Contextual Constraints in Terminological Definitions - San Martín, Antonio (Frontiers in Communication, 2022)
The purpose of a terminological definition is to represent in natural language the most relevant knowledge associated with a term. However, the knowledge activated by a term (i.e., its meaning) varies according to the usage context. Since context is indispensable in meaning construction, knowledge representations in terminological resources must account for it (Faber and León-Araúz, 2016, p. 2). Terminological definitions are no exception. Nonetheless, the recommendation is still that a terminological definition should represent a concept’s necessary and sufficient characteristics, which are regarded as context-independent. Faber (2011, p. 10) argues that a successful knowledge extraction and representation task must be guided by the organization of semantic information in the human mind. Accordingly, this paper proposes a parametrization of the contextual constraints applicable to terminological definitions. in the following types: linguistic, thematic, cultural, ideological, geographical, and chronological. The conscious application of these constraints by the terminologist helps to produce more useful definitions and to avoid inconsistencies and biases.